Tourist behaviour : an international perspective - Kozak, Metin, 1968-; Kozak, Nazmi (CABI, 2016)
This book aims to review and to stimulate interest in a number of emerging and fresh topics in tourist behaviour and experience from a distinctively contemporary perspective. It has been designed to follow a systematic order, following the major stages of the consumer behaviour model. The book has five main parts and 18 chapters. Part I examines the external factors influencing the travel and tourism behaviour of consumers. Part II examines tourist motivations when participating in various tourism- and travel-related activities. Part III deals with tourist decision making and choice. Part IV focuses on tourist consumption and the content of tourist experiences while on a holiday. Part V focuses on the post-consumption/post-experience stage, looking at the issue of how the quality of tourists' experiences contributes to their perceptions, satisfaction and intentions.